Surgical outcome of the transobturator tape procedure for management of female urinary incontinence: A single center experience - Košević Branko; Nikolić Ivica; Bančević Vladimir; Marić Predrag; Jovanović Mirko; Stamenković Dušica; Spasić Aleksandar; Aleksić Predrag (Vojnosanitetski Pregled)
Background/Aim. The transobturator tape (TOT) procedure is considered as a gold standard of surgical treatment option for stress urinary incontinence (SUI). The aim of this study was to determine the efficacy of this procedure in the surgical management of SUI by analyzing a single centre short-term results. Methods. From April 2011 until January 2018, 40 patients with predominantly SUI were operated by the standard TOT procedure. A polypropylene tape was placed in the mid-urethra by a percutaneous transobturator approach. The postoperative assessment considered cough tests and post-void residual urine volume at a week following the operation with additional clinical examination and urine culture at one, three and six months. Results. The mean age of the patients was 58 (42–78) years. Predominantly SUI was present in 32 patients (80%) and mixed urine incontinence in 8 patients (20%). At the initial (one week) assessment, the cough test was positive in 3 patients (7.5%), and 4 patients (10%) needed an indwelling urethral catheter because of voiding difficulties. At the second follow-up, 2 (5%) patients still had a positive cough test, 2 patients (5%) had still the need for an indwelling catheter because of significant postvoid residual (PVR) urine volumes and 2 patients (5%) had a positive urine culture. At the three and six months, postoperative assessment. 3 patients (7.5%) still had a positive cough test. After six months 36 patients (90%) were considered as cured, 1 patient (2.5%) improved and 3 patients (7.5%) were classified as a failure. Conclusion. These results concur with the results of the other published short-term studies that analyzed the surgical outcome of the TOT procedure for female urinary incontinence. This allows us to confirm that the transobturator tape technique is a safe, effective and straightforward procedure after adequate training.